Factors Affecting the Revenue Collection of Prachuap Khiri Khan Municipality Mueang Prachuap Khiri Khan District Prachuap Khiri Khan Province - Thitaree, ฐิตารีย์ (Journal of Information Technology and Innovation, 2020)
The purposes of this research were 1: to study the level of management factors and the efficiency in revenue collection of Prachuap Khiri Khan Municipality Mueang Prachuap Khiri Khan District Prachuap Khiri Khan Province and 2) to study the relation between the management factors and the efficiency in revenue collection of Prachuap Khiri Khan Municipality Mueang Prachuap Khiri Khan District Prachuap Khiri Khan Province. The sample included 358 tax payers within the areas of Prachuap Khiri Khan Municipality. Data were collected using 5-point rating scale questionnaires and checklist and were statistically analyzed in Percentage, Mean, Standard deviation, and Multiple Regression Analysis. The findings revealed as follows. 1. The management factors of revenue collection of Prachuap Khiri Khan Municipality Mueang Prachuap Khiri Khan District Prachuap Khiri Khan Province were generally found at “High” level and the efficiency in revenue collection of Prachuap Khiri Khan Municipality Mueang Prachuap Khiri Khan District Prachuap Khiri Khan Province was generally found at “High” level. 2. The factors in revenue structure, supportive atmosphere for tax payment, the efficiency of tax collectors, and tax law were related to the efficiency in revenue collection of Prachuap Khiri Khan Municipality Mueang Prachuap Khiri Khan District Prachuap Khiri Khan Province at significance level.